2013
DOI: 10.1074/jbc.m112.389536
|View full text |Cite
|
Sign up to set email alerts
|

H2O2 Regulates Lung Epithelial Sodium Channel (ENaC) via Ubiquitin-like Protein Nedd8

Abstract: Background: Proteolytic degradation of epithelial sodium channels (ENaC) assists in regulating net salt and water balance in lung epithelia. Results: H 2 O 2 increases surface expression of ␣-ENaC, transepithelial Na transport, and alveolar fluid clearance via redoxsensitive Nedd8. Conclusion: Redox-sensitive Nedd8 is involved in the ubiquitination of lung ENaC. Significance: Understanding ROS-mediated signaling of lung ENaC is crucial for understanding pulmonary physiology and pathology.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

4
35
0

Year Published

2013
2013
2022
2022

Publication Types

Select...
6
3

Relationship

2
7

Authors

Journals

citations
Cited by 39 publications
(39 citation statements)
references
References 42 publications
4
35
0
Order By: Relevance
“…1). Our studies show that the 65-kD mature and the cleaved form of a-ENaC, which plays a role in HSC-and NSC-mediated changes in transport capacity, was indeed increased after acute CSE exposure (18). Based on this new observation of HSC and NSC activation by CSE exposure, we expect the acute effects of cigarette smoke-induced lung injury to be more severe than, for example, acute LPS-mediate injury because of differences in channel-mediated responses.…”
Section: Single-channel Analysis Of the Effect Of Cse On Ion Transportmentioning
confidence: 59%
See 1 more Smart Citation
“…1). Our studies show that the 65-kD mature and the cleaved form of a-ENaC, which plays a role in HSC-and NSC-mediated changes in transport capacity, was indeed increased after acute CSE exposure (18). Based on this new observation of HSC and NSC activation by CSE exposure, we expect the acute effects of cigarette smoke-induced lung injury to be more severe than, for example, acute LPS-mediate injury because of differences in channel-mediated responses.…”
Section: Single-channel Analysis Of the Effect Of Cse On Ion Transportmentioning
confidence: 59%
“…Previously, we have shown that ENaC is regulated by free radicals, such as superoxide (15) and H 2 O 2 (2,8,16,(17)(18)(19). Therefore, we tested the hypothesis that cigarette smoke extract (CSE) exposure would increase ENaC activity in lung T1 and T2 cells via oxidant signaling.…”
mentioning
confidence: 99%
“…It was also found that mRNA and protein expression of ENaC subunits was significantly increased in the renal cortex of the SS rats fed a high-salt diet (87,152). Since it was previously reported that ROS might be involved in the control of ENaC (47,81,190), these pathways may together act to amplify the development of salt-sensitive hypertension in SS rats. Further studies will be required to link ROS production with these tubular events in the cortex of SS rats.…”
Section: Medullary O 2 ·ϫ No and H 2 O 2 As Determinants Of Blood mentioning
confidence: 91%
“…We have previously reported the effects of a variety of agonists on the biophysical properties of ENaC-in particular, the number of inserted channels and the molecular characteristics of these channels (19,28,29,37,38). ENaC channels are classified based on their selectivity for Na Figures 3D and 4C).…”
Section: Effect Of Hages On Biophysical Properties Of Enacmentioning
confidence: 99%